A Theoretical Note on the Relationship between Documented and Undocumented Migration. (4th August 2011) - Schaeffer, Peter V.; Kahsai, Mulugeta S.
Abstract : Undocumented migration is a (inferior) substitute to documented migration. Hence, policies affecting documented migration also affect undocumented migration. This paper explores this relationship from a theoretical perspective. The implications of this exploration are that lax enforcement of visa rules and national borders, combined with a very long waiting line (small annual quotas) for immigrant visas, can make illegal immigration a preferred option over legal immigration or, more generally, that for policy purposes all types of migrations should be regarded as interdependent. Therefore, policies aimed solely at, say, undocumented immigration will generally be less effective than an integrated policy approach.